The influence of roselle-based wedang uwuh (Hibiscus sabdariffa L.) on SOD (superoxide dismutase) and MDA (malondialdehyde) of cigarette smoke-exposed rat - Tri Dewanti Widyaningsih; Muhammad Fawzul Alif Nugroho (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2021)
Cigarette smoke is the leading cause of several respiratory diseases because it contains high free radical compounds. These free radical compounds can be neutralized with antioxidants obtained from natural ingredients such as roselle. Roselle contains various bioactive compounds and consumes in the form of infusion. Mixing roselle with various herbs as wedang uwuh can increase the antioxidant content. Wedang uwuh is a beverage consisting of various combinations of herbs such as sappan wood, cloves, and cinnamon. This study aims to analyze levels of MDA and SOD in rats exposed to cigarette smoke and given wedang uwuh. This research was conducted on 30 white male Wistar rats that divided into six groups- P0 (normal control), P1 (roselle-based wedang uwuh), P2 (commercial wedang uwuh), P3 (smoke control), P4 (smoke + roselle-based wedang uwuh), P5 (smoke + commercial wedang uwuh). The dose of wedang uwuh is 2.7 ml/kg BW, and the dose of exposure to cigarette smoke is one cigarette for 5 minutes for 30 days. The differences between each group were analyzed using the one way ANOVA test and HSD advanced test. Statistical results showed that giving roselle-based wedang uwuh (P4) significantly reduced MDA levels and increased SOD than the smoke control group (P3). Roselle-based wedang uwuh reduce the MDA levels and increase SOD better than commercial wedang uwuh.